Return migration and socioeconomic mobility in MENA: Evidence from labour market panel surveys - Vladimir Hlasny; Shireen AlAzzawi (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2018)
This study examines the effects of cross-border return migration on intertemporal and intergenerational transmission of socio-economic status across six new harmonized surveys from three Arab countries: Egypt (1998, 2006, 2012), Jordan (2010, 2016) and Tunisia (2014). We link individuals' current outcomes to those in prior years and to their parents' outcomes. We first isolate the outcomes of interest - income, employment status, household wealth based on both productive and non-productive assets, and residence status. Next, we evaluate individuals' socioeconomic mobility over time and across generations as a function of their migration histories. Return migrants, current migrants, and (yet) non-migrants are distinguished. Transitions in individuals' outcomes across years and generations are made functions of pre-existing socioeconomic status, demographics and migration status. Migration patterns are found to differ systematically between Egypt, Jordan and Tunisia, as well as across years. Migration destination is driven by economic, geographic but also historical considerations. Migrant flow from Egypt and Tunisia is highly concentrated, but that from Jordan is much more diffused, on account of job search methods and type of work sought. Egyptian migrants predominantly come from rural areas and disadvantaged governorates, and are less educated, while in Jordan the opposite is the case. Tunisia represents an intermediate case, with migrants slightly less educated but also less likely to be rural than non-migrants. Return migrants find employment in higher earning occupations and are more socially and inter-generationally mobile than non-migrants. However, they outperform non-migrants not only currently, but also in the previous occupation, occupation before previous, and eight years prior, suggesting that individual-level effects and demographics contribute more than migration experience per se. More research is needed to isolate the causal effects of migration spells on migrants' lifetime outcomes.
Keywords: F22; O15; R23; J61; J62; 330; return migration; social mobility; MENA; mobility index